A Framework for Contracted Health IT Performance Assessments. Issue 1 (2nd January 2019) - Martin, Thomas R.; Gasoyan, Hamlet; Wierz, David J.
Abstract: Limited research exists which aids in structuring health IT contracts in an era of performance-based payments. We provide an assessment of common approaches to contracting and measuring of performance in practice. We conducted a review of existing literature and compliment this approach with a survey of healthcare professionals directly involved with health IT systems to further understand and classify current approaches. We identified architypes for structuring healthcare IT performance contracts to include: (1) internal operations, (2) external evaluation and (3) joint agreement for the delivery of value-based care.